The role of radioactive iodine in the management of patients with differentiated thyroid cancer – An oncologic surgical perspective. Issue 5 (May 2020) - Nixon, I.J.; Shah, J.P.; Zafereo, M.; Simo, R.S.; Hay, I.D.; Suárez, C.; Zbären, P.; Rinaldo, A.; Sanabria, A.; Silver, C.; Mäkitie, A.; Vander Poorten, V.; et al.
Abstract: With improved understanding of the biology of differentiated thyroid carcinoma its management is evolving. The approach to surgery for the primary tumour and elective nodal surgery is moving from a "one-size-fits-all" recommendation to a more personalised approach based on risk group stratification. With this selective approach to initial surgery, the indications for adjuvant radioactive iodine (RAI) therapy are also changing. This selective approach to adjuvant therapy requires understanding by the entire treatment team of the rationale for RAI, the potential for benefit, the limitations of the evidence, and the potential for side-effects. This review considers the evidence base for the benefits of using RAI in the primary and recurrent setting as well as the side-effects and risks from RAI treatment. By considering the pros and cons of adjuvant therapy we present an oncologic surgical perspective on selection of treatment for patients, both following pre-operative diagnostic biopsy and in the setting of a post-operative diagnosis of malignancy.